Tachometric Cup Anemometer with Wind Direction Indicator and Fibre-Optic Signal Transmission - Paweł Ligęza; Paweł Jamróz; Katarzyna Socha (Sensors)
This article presents an innovative design of a tachometric anemometer for measuring wind velocity and direction, which does not contain electronic components and systems or power supply systems in the measurement area. This device can be used in extremely unfavourable environmental operating conditions, in locations exposed to direct atmospheric discharges, in conditions requiring restrictive and intrinsic safety, in special military applications, and in measurements in the presence of extreme electromagnetic fields. An innovative optical–mechanical transducer is used in the anemometer. This transducer generates a light pulse signal, the frequency of which is a function of the flow velocity, and the duty cycle is a function of the wind direction. This signal is transmitted via optical fibre from the sensor assembly to the measuring station, located outside the measurement area. The design of the device is simple, durable, and resistant to environmental conditions.